Design and Implementation of a Request and Donation Tracking System for Chronic Disease Patients at the Insan Charity Organization in Zliten (Farajat Service) - Alkshir, Asmaa Mohammad; Barka, Ali Ahmed; ALnaqeeb, Khawla Hassan (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The development of the use of information technology in the field of electronic services, including facilitating the follow-up of needs and donations and obtaining them through the use of the Internet, in addition to the development of many technologies, websites and electronic applications that support this field and facilitate this process. Among the difficulties facing the donation process and obtaining assistance in our society are the lack of credibility and transparency, and the psychological state of those in need. This research aims to design a system to follow up on requests for needs and donations for people with chronic diseases for the Insan Charitable Foundation in the city of Zliten (Farajat Service), to enhance the transparency of operations, build greater credibility and provide support to those in need and patients in an easy and comfortable way. The system allows data to be recorded easily through a digital user interface, and data can be entered and stored in a central and comprehensive manner, which is superior to the traditional system that requires filling out forms manually and can cause data loss and difficulty in accessing it. In addition, case details can be displayed on the site, which encourages a quick response and contributes to facilitating and accelerating the processes of requesting assistance and donations. The research was based on a descriptive analytical methodology to collect and analyze data through tools such as personal interviews and similar websites, and the Waterfall Model was adopted as an executive model for developing the system. The language was used Unified Modeling (UML) for data modeling, the system is characterized by ease of use, quick access to reports, and ensuring the accuracy of operations to avoid errors.